Etnomatematika ANALISIS PEMAHAMAN MATEMATIS TERHADAP DISPOSISI MATEMATIS MELALUI SOAL ETNOMATEMATIKA - arwanto M.Pd; Anan Sunandar; sumliyah sumliyah (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2021)
The study was intended to find out the balance of the ability of mathematical understanding of the mathematical disposition of seventh graders pgri waled district cirebon. The research method used was mixed method research with sequential explanatory design design.. The quantitative data retrieval USES ethnoth-based problems to determine the students' mathematical comprehension capability, which is by combining sundandian culture into triangular and fourth matter. Whereas the dispositional data is taken through angkets created with Google form. Meanwhile, qualitative data are drawn through interview activities with selected subjects from each level of students' mathematical dispositions considering the ability of a student's mathematical understanding. Based on product product coent from Pearson acquired a sig value. (2-tailed) 0.279 > 0.05 then is accepted. Meaning there is no link between the ability of a student's mathematical understanding of the student's mathematical disposition. The result of qualitative analysis is also unequaled in the ability of a mathematical understanding of mathematical dispositions through a matter of sundanese ethnomathematically based culture. Keyword : Mathematical comprehension capability, mathematical disposition, ethnomatemathic